Differences in Eating Habits, Stress, and Weight Changes Among Indonesian Generations Y and Z Students During the COVID-19 Pandemic - Laras Sitoayu; Lintang Purwara Dewanti; Vitria Melani; Putri Azahra Sumitra; Mutiara Rulina Marpaung (Gonabad University of Medical Sciences, 2023)
Background: The COVID-19 pandemic has significantly impacted society and students from various generations. Generations are a group of people who have the same age, traits, and experiences. Not all generations can overcome the impact of the pandemic on themselves, which is the cause of various problems in each generation, influencing on eating habits, behaviors, and stress. Generations Z and Y have reacted greatly to the COVID-19 pandemic. Generation Z is instantaneous, sophisticated, and adaptable to the digital world, while Generation Y is a transitional generation between conventional and digital. The latter is more patient in facing challenges. This study analyzes the differences in eating habits, stress, and lifestyle because of the COVID-19 pandemic in these two generations. Methods: This research was conducted on Indonesian students, divided into groups in terms of Generations Z and Y with a cross-sectional design. The research data was collected online from 237 Indonesian students in April 2021. We used the snowball method for sampling. The analysis of differences was carried out using the independent t-test. Results: The results showed differences in changes in eating habits and stress between the two generations (P<0.05). Generation Y experienced more changes in eating habits compared to generation Z during the pandemic. Additionally, generation Z experienced more stress compared to Generation Y. For weight changes, no difference was observed between the two generations. Each generation experienced weight changes, but it was not significant. Conclusion: Generation Y can better control stress because of the COVID-19 pandemic compared to generation Z. However, with changes in eating habits, generation Y has experienced more changes. Both generations experienced an increase in body weight. There needs to be education and motivation for various generations to face the new normal to not get easily stressed, which can result in changes in eating habits and weight.